Green supply chain management in small and medium enterprises: Further empirical thoughts from South Africa - Louis R. Epoh; Chengedzai Mafini (Journal of Transport and Supply Chain Management, 2018)
Background: For South African small and medium enterprises (SMEs) to gain and maintain competitive advantages and succeed, they have to change their practices and adapt their strategies to the dynamic environment of today. A better understanding and application of green supply chain management practices by SMEs could enable such enterprises to improve their performance and succeed in their operations.